Fe / Fe3O4 nano material loaded with ionic liquid, preparation method of Fe / Fe3O4 nano material and application of Fe / Fe3O4 nano material in electro-catalytic nitrogen reduction
By preparing Fe/Fe3O4-IL modified electrodes, the interaction between ionic liquid and Fe/Fe3O4 nanoparticles was used to solve the problems of insufficient performance and low ammonia production rate of electrochemical nitrogen reduction catalysts, and efficient and stable ammonia synthesis was achieved.
Patent Information
- Application Number
- CN202510090083.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-03-14
AI Technical Summary
The existing ammonia synthesis process requires harsh conditions and relies on fossil fuels, resulting in environmental pollution and energy inefficiency. Electrochemical nitrogen reduction technology limits its practical application due to insufficient catalyst performance and low ammonia production rate.
By preparing Fe/Fe3O4-IL modified electrodes, the interaction between ionic liquid and Fe/Fe3O4 nanoparticles is used to construct a high catalytic activity and selective electrode material to achieve electrocatalytic nitrogen reduction.
The efficiency and ammonia production rate of electrocatalytic nitrogen reduction were significantly improved, the Faraday efficiency reached 29.77%, and good stability was maintained under mild conditions.
Smart Images

Figure CN119615271A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of electrochemical nitrogen reduction, and in particular relates to Fe / Fe 3 O 4 -IL modified electrodes for electrocatalytic nitrogen reduction. Technical Background
[0002] NH 3 It is an ideal energy carrier and the main raw material for agricultural fertilizers. It is mainly produced by the Haber-Bosch process, but this process not only requires harsh conditions (350-550℃, 150-350atm), but also relies heavily on the consumption of fossil fuels and emits a large amount of greenhouse gases. Considering the global energy and climate challenges, there is an urgent need to explore sustainable ammonia synthesis processes to reduce dependence on fossil fuels and mitigate the greenhouse effect. To this end, people have worked hard to develop alternative strategies for ammonia synthesis, such as biological nitrogen fixation, photocatalytic nitrogen fixation, and electrochemical nitrogen fixation. Among these methods, electrochemical nitrogen fixation, as a "green" technology, has shown promising results in N 2 and H 2 O to NH 3 The electrochemical nitrogen reduction reaction uses water as a hydrogen source and can be driven by clean electricity. 3 The production process does not emit any CO2, making it a very promising renewable NH 3 Synthesis method. However, its practical application is greatly limited due to the difficulty of N≡N breaking and the low productivity caused by the existence of competing HER. Therefore, finding electrocatalysts with high catalytic performance is crucial for NRR.
[0003] Iron-based catalysts are one of the most economical and abundant materials in the world, and iron is an important active center in biological nitrogenase, which is beneficial to N 2 However, due to its ferromagnetism and the problems of agglomeration and leaching during the reaction, its application in practice is limited. 2 The unique properties of hydrophobic ionic liquids such as solubility have attracted widespread attention. In addition, hydrophobic ionic liquids can inhibit H 2 O contacts the catalyst surface, which can effectively inhibit the hydrogen evolution reaction and improve the selectivity of NRR. Therefore, ionic liquids as a medium for the nitrogen reduction process are expected to improve the efficiency of electrochemical catalytic synthesis of ammonia. Therefore, in order to develop a new preparation method, designing and constructing high-performance iron-based catalysts is of great research significance for achieving high activity and high selectivity of electrocatalytic reduction of nitrogen to synthesize ammonia. Based on this, this experiment intends to prepare Fe-Fe by a simple chemical synthesis method. 3 O 4Nanoparticles are prepared and the interaction between ionic liquids and nanoparticles is then used to construct electrode materials with high catalytic activity and selectivity for nitrogen reduction. Summary of the invention
[0004] The present invention aims to provide a Fe / Fe electrocatalytic nitrogen reduction system with high catalytic efficiency and ammonia production rate. 3 O 4 -IL modified electrode. The modified electrode showed excellent electrocatalytic activity for electrocatalytic nitrogen reduction, and the obtained Faradaic efficiency and ammonia production rate were both high.
[0005] The technical solution adopted by the present invention is: a Fe / Fe 3 O 4 The nanomaterial preparation method comprises the following steps:
[0006] 1) Put FeSO 4 6H 2 O is dissolved in water and stirred thoroughly to obtain a yellow-green solution;
[0007] 2) Add NaBH to the solution obtained in step 1) 4 The solution was deionized to obtain a black solid, which was washed by centrifugation and dried under vacuum at 60 °C for 24 h to obtain the reaction product;
[0008] 3) Wait for the product Fe / Fe obtained in step 2) 3 O 4 Dissolved in isopropanol, added IL, ultrasonicated at room temperature for 2 h, and then rotary evaporated at 60 ° C to obtain Fe / Fe 3 O 4 -IL.
[0009] The above-mentioned Fe / Fe loaded with ionic liquid 3 O 4 Nanomaterials, by mass ratio, FeSO 4 6H 2 O:NaBH 4 :IL=7:4:2.
[0010] The above-mentioned Fe / Fe loaded with ionic liquid 3 O 4 Nanomaterials, step 2), NaBH 4 The solution concentration is 0.5 mol·L -1 .
[0011] The above-mentioned Fe / Fe loaded with ionic liquid 3 O 4Nanomaterial, in step 3), the ionic liquid IL is 1-butyl 3-methylimidazolium hexafluorophosphate or 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonamide) or 1-butyl 3-methylimidazolium bis(trifluoromethylsulfonamide).
[0012] A Fe / Fe 3 O 4 -IL modified electrode, the preparation method is as follows: 3 O 4 -IL was coated on the surface of hydrophobic carbon cloth and placed at room temperature for 30 min to make Fe / Fe 3 O 4 -IL and the hydrophobic carbon cloth surface are fully combined to produce Fe / Fe 3 O 4 -IL modified electrode.
[0013] The above-mentioned Fe / Fe 3 O 4 -IL modified electrode for electrocatalytic N 2 Converted to NH 3 Application in.
[0014] The above application method is as follows: Fe / Fe 3 O 4 -IL modified electrode was used as working electrode, Ag / AgC1 electrode as reference electrode, platinum sheet as counter electrode, 0.1M Na 2 SO 4 For electrolyte, 0.1MH 2 SO 4 The tail gas absorption liquid was used, nitrogen was introduced into the system, and the electrocatalytic N 2 Converted to NH 3 .
[0015] In the above application, the linear voltammetric scanning method has a scanning rate of 10 mV·s -1 .
[0016] In the above application, in the chronoamperometry, the electrolysis time is 7200 s.
[0017] The beneficial effects of the present invention are:
[0018] 1. Fe / Fe prepared by the present invention 3 O 4 -IL modified electrode, adsorption and activation of N under mild conditions 2 and promote N 2 Converted to NH 3 .Fe / Fe 3 O 4-IL makes full use of the stable morphology of solids and the loading capacity of functional groups, while taking advantage of the enrichment and rapid mass transfer characteristics of liquid substances, achieving efficient synergistic expression of enrichment, catalysis and other functions. This synergistic effect significantly improves the NRR performance, provides novel ideas and methods for the research in the field of electrocatalytic nitrogen reduction, and helps promote further development in this field.
[0019] 2. The present invention controls the technical parameters in the catalytic process and reasonably matches the raw materials of the electrode materials, thereby improving the efficiency of electrochemical electrocatalytic nitrogen reduction, and improving the ammonia production rate and Faraday efficiency. 3 O 4 During the electrocatalytic nitrogen reduction process, the ammonia production rate of the -IL modified electrode was 6.99 μg·h at an applied voltage of -0.5 V (vs. RHE). -1 mg cat -1 , the Faradaic efficiency is 29.77%. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It's Fe / Fe 3 O 4 XRD pattern of .
[0021] Figure 2A It's Fe / Fe 3 O 4 SEM images and Figure 2B isRuFe / Fe 3 O 4 -SEM image of IL.
[0022] Figure 3A It's Fe / Fe 3 O 4 TEM images and Figure 3B It's Fe / Fe 3 O 4 TEM image of -IL.
[0023] Figure 4A It's Fe / Fe 3 O 4 HETEM images and Figure 4B Fe / Fe 3 O 4 HETEM image of IL.
[0024] Figure 5 It's Fe / Fe 3 O 4 Mapping diagram.
[0025] Figure 6 It's Fe / Fe 3O 4 -IL Mapping diagram.
[0026] Figure 7 It's Fe / Fe 3 O 4 and Fe / Fe 3 O 4 FTIR pattern of IL.
[0027] Fig. 8A The UV-visible absorption spectrum curve of different ammonium chloride solutions with known concentrations was tested by indigo blue colorimetry. The absorbance at 655 nm corresponds to NH 4 + concentration.
[0028] Figure 8B is the ammonia calibration curve used to calculate the NH 4 + The concentration of ions.
[0029] Fig.9A The Watt-Chrisp method is used to test the UV-visible absorption spectrum curve of different hydrazine hydrate solutions with known concentrations. The absorbance at 455nm corresponds to the concentration of hydrazine hydrate.
[0030] Fig. 9B The hydrazine calibration curve is used to calculate the concentration of hydrazine hydrate in the electrolyte.
[0031] Fig. 10A It's Fe / Fe 3 O 4 Modified electrode in Ar and N 2 LSV plot under atmosphere.
[0032] Fig. 10B It's Fe / Fe 3 O 4 IT diagrams of electrocatalytic nitrogen reduction of the modified electrode at different potentials for 7200 s.
[0033] Fig. 10C It's Fe / Fe 3 O 4 UV-visible absorption spectra of the modified electrode after NRR reaction at different potentials for 7200s and the electrolyte was developed using the indigo method.
[0034] Fig. 10D It's Fe / Fe 3 O 4 NH production at different potentials of the modified electrode 3 Rate diagram and Faraday efficiency diagram.
[0035] Fig.11 MakeFe / Fe3 O 4 UV-visible absorption spectra of the modified electrode after NRR reaction at different potentials for 7200s and the electrolyte was developed using Watt-Chrisp.
[0036] Fig. 12A It's Fe / Fe 3 O 4 -IL modified electrode in Ar and N 2 LSV plot under atmosphere.
[0037] Fig. 12B It's Fe / Fe 3 O 4 IT diagrams of electrocatalytic nitrogen reduction of -IL modified electrode at different potentials for 7200 s.
[0038] Fig. 12C It's Fe / Fe 3 O 4 UV-visible absorption spectra of the electrolyte after NRR reaction of -IL modified electrode at different potentials for 7200s using the indigo method.
[0039] Fig.12D It's Fe / Fe 3 O 4 NH production at different potentials of -IL modified electrodes 3 Rate diagram and Faraday efficiency diagram.
[0040] Fig.13 MakeFe / Fe 3 O 4 UV-visible absorption spectra of the electrolyte after NRR reaction of -IL modified electrode at different potentials for 7200s using Watt-Chrisp.
[0041] Fig.14 It's Fe / Fe 3 O 4 ,Fe / Fe 3 O 4 -[BMIM]PF 6 andFe / Fe 3 O 4 -[EMIM]NTF 2 andFe / Fe 3 O 4 -[BMIM]NTF 2 Modified electrode Fe / Fe 3 O 4 -[BMIM]PF 6 NH production at -0.3 V (vs. RHE) of the modified electrode 3 Rate diagram and Faraday efficiency diagram.
[0042] Fig.15 It's Fe / Fe 3 O 4 -[BMIM]PF 6 Ammonia yield and Faraday efficiency of the modified electrode under normal conditions at -0.3 V (vs. RHE), open circuit voltage, Ar, and bare carbon cloth.
[0043] Figure 16 is Fe / Fe 3 O 4 -[BMIM]PF 6 It diagram (A), ammonia production rate diagram (B), Faraday efficiency diagram (C) of 5 NRR cycle experiments of the modified electrode at -0.3 V (vs. RHE), and chronoamperometric curve diagram of NRR reaction for 10 h at -0.3 V (vs. RHE) (D).
[0044] Example 1 Fe / Fe 3 O 4 -IL modified electrode
[0045] (I) The preparation method is as follows
[0046] 1)Fe / Fe 3 O 4 Preparation of -IL
[0047] 0.69 g FeSO 4 6H 2 O was dissolved in 100 mL of deionized water and stirred thoroughly to obtain a yellow-green solution; 25 mL of 0.5 mol·L -1 NaBH 4 The solution was washed by centrifugation and dried under vacuum at 60 °C for 24 h to obtain the reaction product Fe / Fe 3 O 4 ; 0.1g Fe / Fe 3 O 4 Dissolve in isopropanol and add 0.025g [BMIM]PF 6 , ultrasonicated at room temperature for 2 h, and then rotary evaporated at 60 °C to obtain Fe / Fe 3 O 4 -IL.
[0048] 2) Electrode pretreatment
[0049] The hydrophobic carbon cloth was cut into a size of 1 cm × 1.5 cm.
[0050] 3)Fe / Fe 3 O 4 Preparation of -IL modified electrodes
[0051] Convert Fe / Fe 3 O 4 -IL was coated on the surface of hydrophobic carbon cloth and placed at room temperature for 30 min to make Fe / Fe 3 O 4 -IL and carbon cloth surface are fully combined to produce Fe / Fe 3 O 4 -IL modified electrode.
[0052] (II) Testing
[0053] Figure 1 It's Fe / Fe 3 O 4 XRD pattern of Figure 1 As shown, 30.2°, 35.9° and 43.8° correspond to Fe 3 O 4 The (220), (311), and (400) crystal planes of Fe and the (110) and (200) crystal planes of Fe at 44.3° and 64.6° respectively indicate that Fe / Fe 3 O 4 .
[0054] Figure 2 is Fe / Fe 3 O 4 SEM images of (A) and RuFe / Fe 3 O 4 -SEM image of IL (B), Figure 2A It can be observed that there are two different morphologies of substances in the material, spherical and flake-shaped. Figure 2B As can be seen in Figure 2, the material can be made more aggregated by adding ionic liquid.
[0055] Figure 3A It's Fe / Fe 3 O 4 TEM images and Figure 3B It's Fe / Fe 3 O 4 -IL TEM image shows that there are two substances with different morphologies in the material, spherical and flake, which corresponds to the SEM result, indicating that two substances with different structures have been successfully synthesized. Figure 3B It can be seen that by adding ionic liquids, the materials can be more aggregated, which is more conducive to the aggregation and reaction of substances.
[0056] Figure 4A It's Fe / Fe 3 O 4 HETEM images and Figure 4B It's Fe / Fe 3 O 4HETEM diagram of -IL, where Figure 4A The lattices of 0.187nm and 0.144nm correspond to the (114) plane of Fe and Fe 3 O 4 The (200) surface of Fe-Fe 3 O 4 Successful synthesis of nanoparticles. Figure 4B In the figure, we can also see that the lattices of 0.187nm and 0.144nm correspond to the (114) plane of Fe and Fe respectively. 3 O 4 (200) face, you can also see [BMIM]PF 6 The circular lattice fringes indicate that Fe / Fe 3 O 4 -IL.
[0057] Figure 5 It's Fe / Fe 3 O 4 According to the detailed data of the map, we can clearly see that the elements Fe and O on the surface are evenly distributed, indicating that the Fe / Fe 3 O 4 Material.
[0058] Figure 6 It's Fe / Fe 3 O 4 -IL mapping diagram. According to the detailed data of the EDS spectrum, we can clearly see that the elements Fe, O, C, N, O, F and P in the Fe / Fe 3 O 4 The surface of the -IL showed a uniform distribution.
[0059] Figure 7 It's Fe / Fe 3 O 4 -IL FTIR spectrum. 568cm -1 The peak at 848 corresponds to the stretching vibration peak of Fe-O, and the peak at 848 corresponds to the stretching vibration peak of PF, indicating that Fe / Fe 3 O 4 -IL materials.
[0060] Example 2Fe / Fe 3 O 4 -IL modified electrode for electrocatalytic N 2 Restoring Applications
[0061] Electrolysis product testing: Ammonia content was tested using the indophenol blue method; hydrazine content was tested using the Watt-Chrisp method; the Faraday efficiency and ammonia production rate were calculated after the content was measured.
[0062] The formula for calculating Faraday efficiency is FE% = (3F × n × V) × 100 / (17 × Q);
[0063] Where F is the Faraday constant and n is the NH 3 is the concentration of the electrolyte, Q is the charge, and V is the volume of the electrolyte.
[0064] The formula for calculating the ammonia production rate is v = (n × V) / (T × m);
[0065] Where n is the NH produced 3 The concentration of V is the volume of the electrolyte, T is the reaction time, and m is the mass of the catalyst.
[0066] The method is as follows: Fe / Fe 3 O 4 -IL modified electrode was used as working electrode, Ag / AgCl electrode as reference electrode, platinum sheet as counter electrode, and 0.1MN 2 SO 4 As electrolyte, 0.1MH 2 SO 4 The three-electrode system was placed in 0.1 M Na 2 SO 4 In the electrochemical determination, a CHI760e electrochemical workstation was used, and the linear voltammetric scanning method was used to determine whether the system could undergo nitrogen reduction and the voltage range in which nitrogen reduction occurred. The scanning rate was 10 mV·s -1 , using the chronoamperometric method to electrolyze nitrogen to convert it into ammonia. Before the electrochemical test, pass N 2 The gas was heated for 30 minutes to ensure that the electrolyte was saturated with the corresponding gas. The solution after electrolysis was measured by ultraviolet light, and the solubility of ammonia was calculated according to the standard curve, thereby calculating the ammonia production rate and Faraday efficiency. The potential was converted to the potential based on the reversible hydrogen electrode as the standard, and according to the Nernst equation ERHE = E Ag / AgCl +0.059pH+0.197V.
[0067] The working electrodes are selected as follows:
[0068] 1) Hydrophobic carbon cloth is the working electrode, marked as CC.
[0069] 2)Fe / Fe 3 O 4 -[BMIM]PF 6 / CC, Fe / Fe 3 O 4-[EMIM]NTF 2 / CC, Fe / Fe 3 O 4 -[BMIM]NTF 2 / CC.
[0070] 3)Fe / Fe 3 O 4 -IL modified electrode: Fe / Fe 3 O 4 -IL is uniformly coated on the carbon cloth and recorded as Fe / Fe 3 O 4 -IL / CC, air-dried and used as working electrode.
[0071] (1)Fe / Fe 3 O 4 -IL electrocatalytic nitrogen reduction
[0072] Before the electrocatalytic nitrogen reduction, the ammonia standard curve of the ammonia standard solution was first determined using the indophenol blue method, and the determination result is shown in Figure 8. The standard curve of the possible byproduct hydrazine was determined using the Watt-Chrisp method, and the determination result is shown in Figure 9.
[0073] Take 60mL of 0.1M Na 2 SO 4 The solution was placed in the two chambers of the H-type electrolytic cell. A three-electrode system was used, with Ag / AgCl electrode as the reference electrode, platinum sheet as the counter electrode, and Fe / Fe as the working electrode. 3 O 4 -[BMIM]PF 6 / CC, Fe / Fe 3 O 4 -[EMIM]NTF 2 / CC, Fe / Fe 3 O 4 -[BMIM]NTF 2 / CC, before electrochemical testing, N 2 The gas was stirred for 30 min to ensure the saturation of the corresponding gas. The electrochemical determination was carried out using a CHI760e electrochemical workstation and chronoamperometric electrolysis for 7200 s. The test results are shown in Figures 10 and 12.
[0074] Fig. 10A , Fig. 12A It's Fe / Fe 3 O 4 andFe / Fe 3 O 4 -IL modified electrode in Ar and N 2LSV diagram under atmosphere. It can be seen from the figure that the modified electrode can undergo electrocatalytic nitrogen reduction reaction between -0.7 and -0.2 V (vs. RHE). Fig. 10B , Fig. 12B Fe / Fe 3 O 4 andFe / Fe 3 O 4 IT diagrams of the -IL modified electrode undergoing electrocatalytic nitrogen reduction for 7200 s at different potentials. Fig. 10C , Fig. 12C Fe / Fe 3 O 4 andFe / Fe 3 O 4 The UV-visible absorption spectra of the electrolyte after NRR reaction of -IL modified electrode at different potentials for 7200s were developed by indigo method. The Faraday efficiency and ammonia production rate were calculated according to the formula. The results are as follows: Fig. 10D , Fig.12D According to the results, Fe / Fe 3 O 4 The ammonia yield and Faraday efficiency of the modified electrode reached their maximum values at -0.30 V (vs. RHE), which were 4.88 μg·h -1 mg cat -1 , 24.94%. In contrast, Fe / Fe 3 O 4 -IL modified electrode reached 6.99 μg·h at the same potential -1 mg cat -1 The maximum ammonia yield and Faraday efficiency of 29.77% were obtained. In addition, the hydrazine content of the electrolyte byproduct after electrolysis at different potentials was measured by UV absorption, such as Fig.11 , Fig.13 Fe / Fe 3 O 4 andFe / Fe 3 O 4 No hydrazine hydrate was detected in the electrolyte after electrocatalytic nitrogen reduction of the -IL modified electrode, indicating that no by-products were generated and it had good selectivity. Fig.14 It's Fe / Fe 3 O 4 ,Fe / Fe 3 O 4 -[BMIM]PF 6 andFe / Fe 3 O 4 -[EMIM]NTF 2 andFe / Fe 3 O 4-[BMIM]NTF 2 Modified electrode Fe / Fe 3 O 4 -[BMIM]PF 6 NH production at -0.3 V (vs. RHE) of the modified electrode 3 Rate diagram and Faraday efficiency diagram, we can see Fe / Fe 3 O 4 -[BMIM]PF6 has the best ammonia yield and Faradaic efficiency. Fig.15 is Fe / Fe 3 O 4 -[BMIM]PF 6 The ammonia yield and Faraday efficiency of the modified electrode under normal conditions at -0.3 V (vs. RHE), open circuit voltage, Ar, and bare carbon cloth. It can be seen that the yield and efficiency under open circuit voltage, Ar, and bare carbon cloth are close to 0, which can be ignored compared to the optimal voltage of -0.3 V (vs. RHE).
[0075] (3)Fe / Fe 3 O 4 Study on the stability of electrocatalytic nitrogen reduction at -IL modified electrodes
[0076] MakeFe / Fe 3 O 4 andFe / Fe 3 O 4 -IL modified electrode at -0.3 V (vs. RHE) 2 Saturated 0.1M Na 2 SO 4 The electrocatalytic synthesis of ammonia was cycled five times to determine its stability. The test results are shown in Figure 16. The results show that Fe / Fe 3 O 4 -IL modified electrode ammonia production rate and Faraday efficiency change little, indicating that the material has good stability. At the same time, the long-term stability of the material was tested and it was found that the material maintained good stability within 10 hours.
Claims
1. An ionic liquid-loaded Fe / Fe3O4 nanomaterial, characterized in that: The preparation method comprises the following steps: 1) Dissolve FeSO4·6H2O in water and stir thoroughly to obtain a yellow-green solution; 2) adding NaBH4 solution to the solution obtained in step 1) to obtain a black solid, washing by centrifugation, and drying under vacuum at 60° C. for 24 h to obtain a reaction product; 3) The product Fe / Fe3O4 obtained in step 2) was dissolved in isopropanol, IL was added, ultrasonicated at room temperature for 2 h, and then rotary evaporated at 60° C. to obtain Fe / Fe3O4-IL.
2. The Fe / Fe3O4 nanomaterial loaded with ionic liquid according to claim 1, characterized in that: In terms of mass ratio, FeSO4·6H2O:NaBH4:IL=7:4:
2.
3. The Fe / Fe3O4 nanomaterial loaded with ionic liquid according to claim 1, characterized in that: In step 2), the concentration of the NaBH4 solution used is 0.5 mol·L -1 .
4. The Fe / Fe3O4 nanomaterial loaded with ionic liquid according to claim 1, characterized in that: In step 3), the ionic liquid IL is 1-butyl 3-methylimidazolium hexafluorophosphate or 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonamide) or 1-butyl 3-methylimidazolium bis(trifluoromethylsulfonamide).
5. A Fe / Fe3O4-IL modified electrode, characterized in that: The preparation method is as follows: Fe / Fe3O4-IL is coated on the surface of the hydrophobic carbon cloth and placed at room temperature for 30 minutes to allow the Fe / Fe3O4-IL and the hydrophobic carbon cloth surface to fully combine to obtain a Fe / Fe3O4-IL modified electrode.
6. Use of the Fe / Fe3O4-IL modified electrode as described in claim 5 in the electrocatalytic conversion of N2 into NH3.
7. The use according to claim 6, characterized in that: The method is as follows: Fe / Fe3O4-IL modified electrode is used as the working electrode, Ag / AgC1 electrode is used as the reference electrode, platinum sheet is used as the counter electrode, 0.1M Na2SO4 is used as the electrolyte, 0.1M H2SO4 is used as the tail gas absorption liquid, nitrogen is introduced into the system, and linear voltammetry scanning method and chronoamperometry are used to electrocatalyze the conversion of N2 into NH3.
8. The use according to claim 8, characterized in that: In the linear voltammetry method, the scanning rate is 10 mV·s -1 .
9. The use according to claim 8, characterized in that: In the chronoamperometry method, the electrolysis time is 7200 s.